METHOD FOR DETERMINING FRICTION FORCES IN PLATE TENSIONERS OF A SEWING MACHINE - Mukhamedjanova, Sabrina (Innovatsion texnologiyalar, 2024)
The article provides information on a method for determining friction forces in disc tensioners of a sewing machine. This article presents calculation schemes for the implementation of plate and spring structures, graphs of the dependence of the friction force between the needle thread and the surfaces of the plates in the plate thread tensioner, as well as graphs of the dependence of the productivity of the sewing machine. This friction force was calculated based on the Amonton–Cloun law. Calculation diagrams of variants of the needle thread plate and spring structures have been completed. A method has been developed for calculating the friction force created by the needle thread with the surfaces of the tensioner plates for existing tensioner designs. A formula has been determined for calculating the friction force between the surface of the needle thread tensioner plates with the recommended conical base and adjustment springs. Graphs were constructed of the dependence of the friction force between the threads and the plates on the tension coefficients of the conical springs of the current design and the tensioner with the recommended double-spring plates. In order to reduce the friction force, the linear components of the conical springs of the thread tensioner, which are mainly recommended for equal values of the coefficients of unity, range from (2,5 ÷ 2,8) · 10ସ݊/݉ , and the nonlinear components are (0.25÷0.30) · It is advisable not to exceed (0,25 ÷ 0,30) · 10ସ݊/݉ଷ .